Effect of carbon and glass fiber posts on the flexural strength and modulus of elasticity of a composite resin - Pereira, Jefferson Ricardo; De Oliveira, Jonas Alves; Do Valle, Accacio Lins; Zogheib, Lucas Villaca; Ferreira, Paulo Martins; Bastos, Luiz Gustavo Cavalcanti (My University, 2011)
The aim of this study was to evaluate the effect of prefabricated fiber posts on the flexural strength and modulus of elasticity of a composite resin. Thirty bar-shaped specimens measuring 25 × 2.0 × 2.0 mm were made, containing posts that were 1.3 mm in diameter and 20 mm long. Each group contained 10 specimens: Group 1, resin without post; Group 2, resin with carbon fiber post; Group 3, resin with glass fiber post. The samples were immersed in water at 37°C until the three-point loading test was performed at a speed of 1.0 mm/minute. The results were statistically analyzed by ANOVA and Tukey's test (P= 0.05). Both fiber posts were similar in strength and both were stronger than the control. Group 3 obtained a higher mean modulus of elasticity than Groups 1 and 2, which were similar. The results of this study demonstrated that the presence of a fiber post significantly raised flexural strength values and the glass fiber post significantly increased the modulus of elasticity of the evaluated composite resin.